Addressing Vaccination Gaps through Student-Led Initiatives: A Study of Stanford Vax Crew’s Impact - Murtagh, Caroline; Gonzalez-Suarez, Aneysis; Zulman, Donna (Journal of Student-Run Clinics, 2024)
Background: Although vaccines are critical to disease prevention, substantial gaps persist in adult vaccination coverage in the United States due, in part, to material and social barriers. Farmworkers face unique challenges to accessing vaccination services, such as migratory residence, immigration status, low levels of insurance, and geographic distance from clinics, many of which were exacerbated during the coronavirus disease 2019 (COVID-19) pandemic. Student-driven, community-focused programs offer a potential mechanism to enhance vaccine equity. Stanford Vax Crew is a student-led organization that partners with community organizations to host pop-up vaccine clinics, which aim to (1) address the material barriers that impact vaccination status, (2) establish trust in vaccine services, and (3) equip future medical professionals with skills to engage in community health initiatives. Methods: This paper describes the strategies used by the organization to reach surrounding communities with vaccines, especially agricultural workers. It assesses the reach of the program through analysis of demographic data collected at pop-up clinics. Results: From August 2021 to March 2023, the majority of COVID-19 vaccine recipients were middle-aged adults (61%) of Hispanic ethnicity (82%) working in the agricultural, forestry, or fishing industries (58%). In total, 1377 COVID-19 vaccines were administered by Stanford Vax Crew. Conclusions: Findings suggest that Stanford Vax Crew’s partnerships with diverse institutions helped facilitate access and build trust, thereby enhancing vaccine uptake. Partnership with agricultural employers and community-based organizations targeted farmworkers, which enabled the group to host clinics on farms immediately before and after work hours, which proved especially effective for reaching agricultural workers.